The Role of Democratic Law and Theory of Society in the Work of J. A. Schumpeter: To the 140th Anniversary of Birth of Worlds Famous Economist, Lawyer, Historian, Politician, Social Philosopher and Humanist - Jiří Bíly (Journal on European History of Law)
The article called Marking the 140th anniversary of prof. Dr. J. A. Schumpeter’s birth. The author describes Schumpeter’s scientific works his opinion on Marx’s theories of capitalism, as well as the deep humanism of this extraordinary man, reflected in his attitude towards the people of lower status in general. The article talks about Schumpeter’s theories on the role law in the case with the interplay between law and economy, the interrelationship between law and politics. In the context of democratic society, law appears as one of the most central mechanism to ensure that the participation of the populace in a state’s governance, as well as the outcome of government in the form of legislative decisions, abide by standards of democracy.